2011
DOI: 10.1038/tpj.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-9 polymorphisms affect plasma MMP-9 levels and antihypertensive therapy responsiveness in hypertensive disorders of pregnancy

Abstract: Abnormal matrix metalloproteinase (MMP)-9 levels may have a role in hypertensive disorders of pregnancy. We examined whether MMP-9 genetic polymorphisms (g.À1562C4T and g.À90(CA) 13À25 ) modify plasma MMP-9 and tissue inhibitor of metalloproteinase (TIMP)-1 levels and the responses to antihypertensive therapy in 214 patients with preeclampsia (PE), 185 patients with gestational hypertension (GH) and a control group of 214 healthy pregnant (HP). Alleles for the g.À90(CA) 13À25 polymorphism were grouped L (low) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 35 publications
(50 reference statements)
1
41
3
Order By: Relevance
“…On the contrary to the results of the current study, they reported that C1562T polymorphism may correlate with gestational hypertension. Nevertheless, another study reported that T allele for the C1562T polymorphism is associated with gestational hypertension (Palei et al 2012). In a study conducted by Lacchini et al (2010) the authors determined that the frequency of 1562 CC genotype, CT genotype and TT genotype was 75, 25 and 0 %, respectively, in hypertensive patients, while corresponding frequencies were 80, 18 and 2 % in control subjects.…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary to the results of the current study, they reported that C1562T polymorphism may correlate with gestational hypertension. Nevertheless, another study reported that T allele for the C1562T polymorphism is associated with gestational hypertension (Palei et al 2012). In a study conducted by Lacchini et al (2010) the authors determined that the frequency of 1562 CC genotype, CT genotype and TT genotype was 75, 25 and 0 %, respectively, in hypertensive patients, while corresponding frequencies were 80, 18 and 2 % in control subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, several studies have reported an association between MMP-9 genetic polymorphism and the development of pre-eclampsia; however, the results of these studies are inconclusive (Coolman et al, 2007;Fraser et al, 2008;Palei et al, 2010Palei et al, , 2012Luizon et al, 2012;Rahimi et al, 2013Rahimi et al, , 2014Rahimi et al, , 2015. Some studies suggested that the CC genotype or C allele of MMP-9 -1562 C/T is associated with increased risk of developing pre-eclampsia in Caucasian pregnant women (Coolman et al, 2007;Luizon et al, 2012;Rahimi et al, 2013Rahimi et al, , 2014Rahimi et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…We reported associations of some genotypes and haplotypes formed by these polymorphisms with PE and/or gestational hypertension (GH). [18][19][20][21] These studies indicate that, at least individually, these genes may be important to the development of these disorders. Besides the study of these genes independently, epistasis has also been suggested to be an important component of complex diseases, including PE.…”
Section: Introductionmentioning
confidence: 84%
“…Seven clinically relevant polymorphisms were studied in eNOS (T-786C, rs2070744 in the promoter region; the 27 bp variable number of tandem repeats in intron 4; and Glu298Asp, rs1799983 in exon 7), in the promoter region of MMP-9 (C-1562T, rs3918242 and -90(CA) [13][14][15][16][17][18][19][20][21][22][23][24][25] , rs2234681), and in the promoter region of VEGF (C-2578A, rs699947 and G-634C, rs2010963). Genotypes for eNOS rs2070744 and rs1799983 and for VEGF polymorphisms were determined by TaqMan allele discrimination assays using probes and primers designed by Applied Biosystems (Carlsbad, CA, USA), as previously described.…”
Section: Genotype Determinationmentioning
confidence: 99%
See 1 more Smart Citation